The relationship between body mass index and musculoskeletal disorders among tailors - Dewa Ayu Agung Megaretha Ayunindya; Ni Wayan Tianing; I Made Niko Winaya; I Made Muliarta (Physical Therapy Journal of Indonesia, 2023)
Background: Humans have a demand to have more abilities so that the role produced is as desired. Muscles and bones are important for workers to do their jobs. Complaints related to muscles and bones can be called musculoskeletal disorders. Body mass index (BMI) is one of the factors influencing the incidence of musculoskeletal problems. This is because people with a high score of BMI will try to support their weight by tightening the muscles in their lower back. On the other hand, if this happens frequently, the spinal cord pads will be under a lot of pressure. This study aimed to establish a relationship between BMI and musculoskeletal disorders. Methods: This study used analytic observational cross-sectional research as the study design. Were 53 individuals used as samples in this study utilizing a purposive sampling method based on exclusion and inclusion criteria. Results: Data on BMI and musculoskeletal disorders were analyzed using the Pearson correlation test, which found a significant correlation of p=0.000 (p<0.05). Conclusion: Based on the study's results, it can be concluded that there was a relationship between BMI and musculoskeletal disorders among tailors in Denpasar City.